The effect of torrefaction on the properties of spruce (Picea abies) and sycamore (Acer platanoides) wood - Spirchez Cosmin; Lunguleasa Aurel (Revista Applied Sciences, 15,10054, 2025)
The recent increase in demand for natural wood has led to an increase in the study of various wood treatments to expand its applications. In this regard, the torrefaction of natural wood has been used to complement classic treatments, reducing the wood’s affinity for water and increasing its durability while maintaining or only slightly worsening its physical and mechanical properties. The aim of this paper is to evaluate the physical and mechanical properties of spruce and mountain maple wood torrefied at temperatures of 180–200 ◦C for 1–3 h and to compare them with those of non-torrefied wood of the same species. The results showed that torrefied wood has better properties in terms of water affinity and has quite good properties in terms of density and the analyzed mechanical properties such as compressive strength, tensile strength parallel to the wood grain, static bending strength, and Brinell hardness. The general results of this paper show that the torrefied samples of the two species have better properties than non-torrefied samples, thus broadening their applications